Kesuksesan Penyandang Disabilitas Fisik dalam Berwirausaha di Kota Padang - Yunrizal, Lathifah; Fatmawati, Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2022)
This study examines the success of people with physical disabilities in entrepreneurship in the city of Padang. The purpose of study is to describe the process of success for people with physical disabilities in starting a business and as inspiration for other people with disabilities to be start their own business. This study uses qualitative research with a qualitative descriptive approach, using observation, interviews and documentation. The results of this study indicate that the importance of intrinsic and extrinsic factors in self-acceptance for people with physical disabilities, being inspired to start a business, a business that has been run into a job for someone, and the product being worked on are also able to compete with products owned by non-persons. disability. The conclude is people with physical disabilities are also able to succeed in starting a business with their own desires and motivation from others.